Quantitative assessment of groundwater resources and aquifer hydraulic properties using combined geophysical techniques, in North Gemas, Malaysia - Egbenda Juanah, Mohamed Sahr (2012)
With Malaysia increasingly becoming an industrialized nation, the need for quality water to meet its domestic and industrial requirements is becoming a major challenge, since most of the surface waters are experiencing an increase in pollution and/ or contamination due to industrialization and agricultural activities. Groundwater exploration has become more and more important as most of it is often safe from pollution. Thus, the research aims to develop a much broader understanding of the nature of groundwater potential in the study area and its relations with the local geology. Laboratory and combined geophysical techniques such as multi-electrode resistivity, induced polarization, and borehole geophysical techniques were carried out on volcano-sedimentary rocks as part of the groundwater resource's investigations. The result obtained identifies fractures and/or assures and different lithological units. Two types of aquifer systems in terms of storage were also identifed within the area; one within a fracture system (tu), and an intergranular property of the sandy material. The result reveals that the aquifer occupies a surface area of about 3250555 m2 with a mean depth of 43.71 m and a net volume of 9.798 x107m3. From the approximate volume of the porous zone (28%) and the total aquifer volume, a usable capacity of (274:339.30:177) x 107m3 of water in the study area can be deduced. Increase in demand for the protection, remediation and sustainable management of groundwater resources have resulted in an increased need to determine accurately the distribution of aquifer hydraulic parameters. The use of combined geophysical and hydrological measurement have been proven to be less invasive as compared to the traditional pumping test, which provide information only close to the boreholes and the sample locations. As a result of this, an empirical function between the geoelectrical resistivity of an aquifer and hydrogeological investigations was established to estimate the aquifer hydraulic properties through the use of Kozeny-Carman- Bear equation. The reported mean geometric hydraulic conductivity value for the aquifer under investigation is (8.67 x 10-3 m/s or 31.2m/day), and the estimated average transmissivity is (2.03 x 10-1 m2s or 73m2/day). The groundwater and surface water analyses shows that present status of groundwater quality in Kg Londah and its environs is suitable for industrial, drinking and irrigational purposes. Hence, the study provides useful information that can be used to develop a much broader understanding of the nature of groundwater potential in the area and its relationship with the local geology.